Earthquakes yes, disasters no - Alik Ismail-Zadeh (npj Natural Hazards)
Abstract To answer the question of why seismic hazards turn into disasters, I provide here an overview of studies on the lithosphere dynamics, seismic hazard assessments, earthquake-triggered hazards, forecasting of large earthquakes, vulnerability and resilience assessments, and risk communication. Knowledge gaps in these fields are discussed. Integrated research on risks of earthquake-triggered disasters is essential in producing useful and usable knowledge for informed decision-making to reduce disaster risks.